Synthesis of iron oxide nanoflakes at lower temperature by air oxidation of iron foils - Mohamed Rashid, Norhana (IOP Publishing, 2014)
Iron oxide α-Fe2O3 nanoflakes have been synthesized on iron foil by a simple air oxidation process. Dry air flows constantly over the iron foils during the oxidation process in the temperature range of 350–600 °C with annealing periods of 1–6 h. Large quantities of nanoflakes with average tip and bottom diameters of 40 and 140 nm, respectively, and average lengths of 200 nm were obtained at a temperature of 450 °C and 6 h of annealing. These nanoflakes had a preferential growth direction of (110) with a 0.25 nm fringe spacing. Their surface morphology, phase purity, and crystal structures were confirmed by scanning electron microscopy (SEM), X-ray diffraction (XRD), and transmission electron microscopy (TEM) analysis. Good-quality iron oxide nanoflakes can be obtained by optimizing the growth temperature and annealing period. Surface diffusion of iron atoms and iron oxide molecules was believed to be the growth mechanism of the nanoflakes because of the low oxidation temperature used.